The Effect of COVID 19 Pandemic on ClinicalPractices and Education in Cukurova University Faculty of Dentistry - Yurdanur Uçar; Koray Soygun (Ankara University, 2021)
Purpose:The aim of this study was to evaluate the strategy of Cukurova University Faculty of Dentistry in clinicalmanagement and education during COVID 19 pandemic and report the effects of the coronavirus outbreak that affectedthe whole world. Methods:The number of patients, income and expenditure rates were compared between March-November 2019 andMarch-November 2020. The effect of COVID 19 pandemic on education was evaluated by comparing the preclinical andclinical course methods and assessment-evaluation methods before and during the pandemic period. Comparisons weremade considering the theoretical and the practical training, feedback and student evaluation methods. Results:The number of patients and income levels in March 2020 was approximately 50% of the income in March 2019.A dramatic decrease was observed in the number of patients and income-expense levels in April and May. Althoughnormalization has started by October 2020, clinics have been working with a performance of approximately 40%compared to 2019. Cukurova University Faculty of Dentistry does the online dental training using Microsoft Teams.Practical applications are thought using videos and photographs. Feedback is important in practical training. For thisreason, students are asked to prepare a powerpoint presentation with pictures taken in a pre-determined format andsubmit the presentation through the software. The lecturer gives feedback using the Microsoft Teams program. Onlineexams (multiple choice, structured open ended or oral) are conducted using the same software. Conclusion:Cukurova University, Faculty of Dentistry is affected by COVID 19 pandemic. However, the minimal impactof COVID 19 pandemic has been targeted. Therefore, the effective clinical arrangements and rapid adaptation to thedistance learning was needed. Pandemic gave us a new vision for dental practices which will be used in the postpandemic period and help us reconsider our previous working habits.